Analisis Isu Dan Masalah Pembangunan Ekonomi Provinsi Kepuluan: Studi Kasus Isu Dan Masalah Pembangunan Ekonomi Provinsi Maluku - Desry J. Louhenapessy (Moneter : Jurnal Ekonomi dan Keuangan, 2023)
One of the problems in economic development is the low level of connectivity between regions. This is the root of the problem of economic development in the archipelagic regions in Indonesia which is still lagging behind, so it has a big impact on the people. Even though it has enormous natural resource potential, in general the people in this island province are still poor. Many of the development goals implemented have not been achieved because there are still obstacles faced in the development process itself. This is actually the challenge of development to improve the welfare of the Indonesian people in general and the people in the archipelago region in particular. Various issues and problems are the biggest challenges to development, therefore it is very necessary to have appropriate solutions to overcome these various issues and problems so that development for the welfare of the people in the archipelago can run smoothly and the set development goals can be achieved.